1975
DOI: 10.1113/expphysiol.1975.sp002305
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin in Rabbit Bile: Its Relation to Iron Metabolism

Abstract: The relation of biliary lactoferrin concentration and the iron status of the body was studied in normal, anaemic and iron-loaded rabbits. In anaemic rabbits lactoferrin concentrations rose to two to three times the original values. Loading with iron resulted in a return to normal values. Mobilization of iron with desferrioxamine also gave a rise in lactoferrin concentration in bile. Lactoferrin may have a regulatory function in situations of enhanced iron absorption or mobilization of iron from depots.Lactofer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In contrast, rabbits to who iron was administered, even in low doses, showed inhibition of lactoferrin secretion in the bile. Thus, lactoferrin might have a control function in situations when increased amounts of iron are released from its depots (Van Vugt et al, 1975). A similar relationship between lactoferrin from the duodenal secretion and iron metabolism was found in humans (De Vet and Van Gool, 1974).…”
Section: Lactoferrin and Iron Metabolismmentioning
confidence: 52%
“…In contrast, rabbits to who iron was administered, even in low doses, showed inhibition of lactoferrin secretion in the bile. Thus, lactoferrin might have a control function in situations when increased amounts of iron are released from its depots (Van Vugt et al, 1975). A similar relationship between lactoferrin from the duodenal secretion and iron metabolism was found in humans (De Vet and Van Gool, 1974).…”
Section: Lactoferrin and Iron Metabolismmentioning
confidence: 52%
“…The amino acid compositions of bovine Lf and human Lf show 69% sequence homology (6). Lf appears to play a role in many biologic processes, including the proliferation and differentiation of enterocytes (7), regulation of iron absorption (8), antimicrobial activities (9), immunomodulation and anti-inflammatory responses (10), and antivirus or anticancer activities (11). Lf is considered to be an antioxidant because of its ability to bind two atoms of iron, which is important in the formation of free radicals (12).…”
mentioning
confidence: 99%
“…In vitro experiments with exogenous apolactoferrin indicated that this protein inhibited accumulation of iron in the intestinal wall but did not block net iron transfer to the serosal surface. Similar data by van Vugt et al (1975) indicated that lactoferrin may play a regulatory role in iron absorption; specifically, a protective function when increased iron absorption is necessary or when excess iron intake occurs.…”
Section: Non-heme Proteinsmentioning
confidence: 54%
“…The name lactoferrin is, however, misleading. Although it was first isolated from milk, lactoferrin has since been isolated from saliva and pancreatic fluids (Masson and Heremans, 1966a), bile (van Vugt et al , 1975), semen (Roberts and Boursnell, 1975), lacrimal fluid (Broekhuyse, 1976) and uterine secretions (Dixon and Gibbons, 1979).…”
Section: Non-heme Proteinsmentioning
confidence: 99%